THE ROLE OF TECHNOLOGY IN MODERN EDUCATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
The present article provides with information about the benefits of technology in a modern world of education.